pencemaran air sungai yang di sebabakan oleh penggunaan pestisida berlebih dan limbah yang di buang sembarangan - Nening Listari; Maya Ekaningtias (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2025)
This study aims to determine the physical quality test of antiseptic solid soap made from betel leaf extract (Piper betle L.) as a natural antiseptic with the addition of dragon fruit peel extract (Hylocereus polyrhizus) as a natural dye. The method used was an experimental method with a Randomized Block Design (RBD). The parameters tested for physical quality included pH, foam height, and organoleptic (color, aroma, texture, and skin preference). The saponification process with varying concentrations of betel leaf extract and dragon fruit peel produced ten formulations (F1–F10). Physical quality tests included measuring pH, foam height, and organoleptic tests by 10 panelists. The results showed that all formulations met the SNI 3532:2021 standard, with a pH of 7–11, an average foam height of 6.7–11.3 cm, and the highest organoleptic score at F8 (average aroma value of 4.5; skin preference of 4.4) by 10 panelists.